THE INFLUENCE OF BRAND EXPERIENCE AND PERCEIVED QUALITY ON BRAND LOYALTY IN ST.IVES PRODUCTS IN DKI JAKARTA THROUGH BRAND TRUST - Tasya Adiba Kamilah; Galuh Mira Saktiana (International Journal of Application on Economics and Business, 2026)
This research has a purpose to test the affect brand experience, perceived quality, and brand trust on brand loyalty for St.Ives products in the people of DKI Jakarta. Sampling technique is non-probability, with purposive sampling with 260 participants, and used analyze data with SEM PLS. The results of this research are positive and significantly influence on brand experience, perceived quality, and brand trust on brand loyalty for St.Ives products in the DKI Jakarta community. Brand trust not mediate brand experience and perceived quality on brand loyalty. This shows that brand experience, Perceived Quality, and brand trust have a dominant affect in encouraging the loyalty of the people of DKI Jakarta to St.Ives products. Brand trust, although it has a positive affect, is not significant, which indicates that although customers believe in a particular brand, it is not strong enough to influence their behavior or decisions. The result emphasize the importance of build loyalty to consumer.